Implementasi Teknik Rotoscope dan Cel Shading Pada Pembuatan Animasi 2D - Rendy Daffa Wardhana; Agusdi Syafrizal; Yusni Nyura (CV MEDAN TEKNO SOLUSI, 2025)
2D animation with the Rotoscope Technique is a form of artwork that can be used to convey social messages, such as about bullying. Bullying is aggressive behavior that is carried out repeatedly and deliberately to hurt or dominate others. Bullying can have a negative impact on both the victim and the perpetrator, such as lowering self-confidence, causing depression, or even suicide. Therefore, there needs to be efforts to prevent and overcome bullying in the school and community environment. The purpose of this study is to make a 2D animated short film that raises the theme of the causes of bullying using the Rotoscope Technique and the Cel Shading Technique. The author uses the Rotoscope Technique to give a realistic and dramatic impression to the characters and backgrounds. The Rotoscope technique is an animation technique that uses a computer to redraw frame by frame on top of an existing video recording or moving image. The Cel Shading technique is a coloring technique that uses the selection of colors with strong contrast. The production process uses the Clip Studio Paint application, Adobe Premiere Pro, CorelDraw and FL Studio, the result of this research is a 2D animated short film entitled